Application of biomass-derived hydrochar in process stability of anaerobic digestion. (February 2022) - Ayodele, Olubunmi O.; Adekunle, Abiodun E.; Alagbe, Olajumoke A.; Anguruwa, Gloria T.; Ademola, Adeola A.; Odega, Chioma A.; Dornack, Christina
Abstract: Stability and in-situ upgrading of biogas in anaerobic digestion (AD) processes using biomass-derived hydrochar as a cheaper alternative is presented. The influence of hydrochar on AD of organic fractions of municipal solid wastes (OFMSWs) was conducted at OLR of 1 kg VS/[m 3 .d]). The biochemical methane potential of hydrochar was insignificant while digester amended with 20% hydrochar had a longer lag phase, producing biogas after the third day of AD. The total volume of biogas of 464.29 NI/kg oTS in digester containing both OFMSWs and hydrochar was higher when compared with digester without hydrochar (257.62 NI/kg oTS). Likewise, the methane content of digester containing hydrochar was 10% higher. The pH and electrical conductivity in amended digester declined daily from 8.36 to 7.31 and 17.12 to 8.15 mS/cm, respectively. The stability indicators responded positively to the addition of hydrochar to OFMSWs, outperforming other digesters treated with only hydrochar or OFMSWs. Graphical abstract: Unlabelled Image Highlights: Coffee Ground Residue (CGR) is converted to hydrochar via hydrothermal carbonization. Hydrochar was used as additive in anaerobic digestion (AD) of OFMSW. Hydrochar shortened the lag phase and increased the degradation of the OFMSW. Use of hydrochar from CGR increased methane content of biogas thus improving quality.